Farmers Helping Hand Application - Nagarajan, Ramthanaraj; Mohd Yunus, Mohd Amin (Applied Information Technology And Computer Science, 2023)
Farmers Helping Hand Application is an application which act as a educational platform for the farmer’s for Radza and Son’s farm. The purpose of developing this application is to solve the problem of Radza and Sons farm in training their farmers to produce quality fruits. This application will provide information to the farmer regarding correct way of planting specific fruits. To ensure farmers can follow the procedures, scheduling features included which help farmers follow the daily task assigned on planting fruits. Despite that to clarify farmer’s doubts, forum features included to make sure they could interact with other users and clear their doubts. The developed application also included weather forecast features to provide clarity among the farmers on the weather daily which will help them to organize their plantations well. To secure the privacy of the users, login method of One Time Password (OTP) implemented. Waterfall model which consists of six phases is used to assist this project development. The development of this application will assist the owner and farmers to produce more quality fruits which could increase their sales consecutively.